Effect of polarization rotation on the optical and photovoltaic properties of BiFeO3 thin films. (5th July 2021) - Hu, Yiqi; Abdelsamie, Amr; Weng, Yuyan; Zheng, Fengang; Fang, Liang; You, Lu
Abstract: Visible-light-active ferroelectric materials are gaining increasing attention due to the unique ferroelectric photovoltaic effect. To boost the light harvesting capability, vast research is devoted to band gap engineering by chemical substitutions, regardless of the side effect on ferroelectric polarization. Here, we focus on how polar order affects the optical and photovoltaic properties. Using BiFeO3 as the model system, we induce the polarization rotation by A-site La substitution, which results in continuous reduction of optical anisotropy of the samples, as revealed by the concerted optical characterizations. This further causes the decrease of angular dependence of ferroelectric photovoltaic effect on the light polarization. The results demonstrate the inner connection of the ferroelectric polarization and optical anisotropy via the lattice degree of freedom.